Advanced Pore Structure Analysis of Silver Nanoparticles via Electron Microscopy: Implications for Functional Optimization - Singh Preetjot; Ojha Varun; Sharma Prashant; Mittal Aman; Nautiyal Rishi Dev; Bandhavi Ch.; Singh Sandeep; Hamza Laeth H.J. (E3S Web of Conferences)
In this paper, quantitative analysis of the pore structure of AgNPs is presented by combined analysis of advanced electron microscopy techniques. The synchrotron-based analysis of silver nanoparticles with 18-30 nm in size confirmed detailed information about the internal structure of their porous nature of the nanoparticles and their surface characteristics. Although the pore volume of AgNPs changed from 28 nm³ to 40 nm³, pore size ranged between 3 nm to 10 nm. Specific pore volume values referring to AgNP mass were within 10–26 nm 2 /g depending on nanoparticle size. Furthermore, the surface area values varied between 25 m²/g and 50 m²/g evidencing the influence of nanoparticle size on internal as well as exterior surface area. Taken together, the findings suggest a direct dependency of size dependent nanoparticle on the pore structure and surface area of the support material: Diameter of AgNP has direct impact on porosity of the samples. These findings are useful for optimizing internal porosity and surface properties of AgNPs for particular uses such as catalysis, drug delivery, and sensing. This vast study provides a framework for synthesising AgNPs with any types of pore structures to improve nanotechnology applications through careful tailoring of materials.